pH effect on the synthesis of different size silver nanoparticles evaluated by DLS and their size-dependent antimicrobial activity - Gontijo,Leiriana Aparecida Pinto (2020)
ABSTRACT This paper reports citrate-stabilized silver nanoparticles (AgNPs) synthesized by nitrate ion chemical reduction with sodium borohydride, at different pHs (2–9). The AgNPs synthesized by this method exhibited size distribution from 5 to 249 nm, depending on pH, as determined by dynamic light scattering, and morphology spherical, as determined by transmission electron microscopy. In pH range 3–7 occurred aggregation of the nanoparticles. The size distribution depending on pH was determined by dynamic light scattering. The zeta potential was determined, and the colloidal stability was correlated with nanoparticles aggregation at different pHs. The size-dependent antimicrobial activity was evaluated for two solutions, wherein both samples exhibited antimicrobial activity, although the smallest AgNPs without agglomeration have enhanced antimicrobial properties.